Somatotype and stress hormone levels in young soccer players - Handziska, E.; Handziski, Z.; Gjorgoski, I.; Dalip, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: The relationship between somatotype and cortisol and adrenocorticotropic (ACTH) hormone concentrations at rest or after exercise in adolescent soccer players at different time points throughout a soccer season is not understood. Therefore, the aim of this study was to examine the relationship between somatotype and cortisol and ACTH concentrations at rest and after exercise in adolescent soccer players at different time points during a soccer season.